1986
DOI: 10.1111/j.1476-5381.1986.tb10266.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural and adrenocortical responses to nicotine measured in rats with selective lesions of the 5‐hydroxytryptaminergic fibres innervating the hippocampus

Abstract: 1 The effects of acute and subchronic (7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 27 publications
3
4
0
Order By: Relevance
“…Our results showing no significant anxiogenic effect below 0.5 mg/kg are in broad agreement with those of Balfour et al (1986), who found no effects with 0.4 mg/kg of the racemate [which would be equivalent to a lower dose of the (-)-enantiomer because the (+)-enantiomer has little action on rat nicotinic receptors in the brain (Brioni et al 1997)]. However, our results contrast with the anxiolytic effect reported by Brioni et al (1994) after injection of 0.3 mg/kg nicotine.…”
Section: Discussionsupporting
confidence: 95%
“…Our results showing no significant anxiogenic effect below 0.5 mg/kg are in broad agreement with those of Balfour et al (1986), who found no effects with 0.4 mg/kg of the racemate [which would be equivalent to a lower dose of the (-)-enantiomer because the (+)-enantiomer has little action on rat nicotinic receptors in the brain (Brioni et al 1997)]. However, our results contrast with the anxiolytic effect reported by Brioni et al (1994) after injection of 0.3 mg/kg nicotine.…”
Section: Discussionsupporting
confidence: 95%
“…This result is also consistent with previous findings indicating that serotonin and DA play a critical role in the control of Nic SA (Balfour et al. , 1986; Corrigall & Coen, 1989; Corrigall, 1992; Olausson et al.…”
Section: Discussionsupporting
confidence: 94%
“…Therefore, using the elevated plus-maze, which has the ability to detect the anxiogenic as well as anxiolytic effects of drugs (Pellow et al, 1985), the possibility that ibogainepretreated animals experience anxiety when they are subsequently exposed to nicotine was investigated. Consistent with previous reports (Balfour et al, 1986), nicotine itself did not produce effects which would be indicative of anxiolysis nor anxiogenesis in this behavioural test although nicotine did result in a very significant increase in the overall activity of both the vehicle and ibogaine-pretreated rats. Furthermore, there was no change in the overall activity of the saline-treated control rats which could be attributed to their receiving an injection of ibogaine 22h previously.…”
Section: Discussionsupporting
confidence: 92%